Cold-active Pseudomonas Lipases for Improving Cheese Ripening at Low Refrigeration Temperatures - Palani, Dilsher M R (Journal of Science in Medicine and Life, 2025)
The traditional ripening of semi‐hard cheeses at a temperature of 12–15 °C is both consuming energy and takes time. In this work, a cold-active lipase from Pseudomonas spp. for use as an accelerator of ripening at 8 °C. Cheese vats were manufactured without the addition of lipase (control), with a commercial thermostable lipase (150 U kg⁻¹) and cold lipase at two concentrations (150 and 250 U kg⁻¹). FFA content, instrumental hardness and trained-panel sensory scores were recorded over a period of 60 days. Cold lipase at 150 U kg⁻¹ doubled FFA levels compared with control (3.1 vs 1.9 mg g⁻¹), decreased hardness by 45 % and resulted in the greatest consumer acceptability (8.2 ± 0.1 on a 9 point scale). A higher dose (250 U kg⁻¹) further disrupted texture but introduced some bitter end-note. Modelling of energy use suggested that a saving in the range of 15–20 kWh t⁻¹ was possible by maintaining the ripening room at 8 °C. Pearson correlations showed that an increase in lipolysis was strongly linked to a softer texture and a higher flavour acceptance. The results are favorable to immobilized Pseudomonas lipase moderate dosing as an economical method to reduce cold ripening duration without negative sensory quality results and, when appropriate, where sensory quality is even improved.